Revisiting retail planning policies in countries of restraint of Western Europe. Issue 3 (1st September 2016) - Guimarães, Pedro
ABSTRACT: Retail planning became more relevant following a number of notable changes that affected the retail sector. Among several other reasons, the peripheral location of new retail formats and the concentration in larger retail companies have had negative impacts on town centres and in the traditional retail structure. In this paper, we review the evolution of the main elements and axes of intervention in retail planning in England, Sweden, Denmark, Germany and the Netherlands. We also establish a retail planning definition that could be applied to the different national contexts. It is concluded that, although there is a similarity between the objectives of the policies implemented, the instruments applied are diverse and dependent on the evolution of societal characteristics, as well as political and ideological beliefs.